Web-Based Employee Performance Assessment Using Graphic Rating Scales Method At PT. STAR MULTI - Meiarni Situkkir (Jurnal Teknik Indonesia, 2024)
Work assessment or performance evaluation in a company is an effort to identify various weaknesses and strengths of employees as a basis for improving all weaknesses and strengthening strengths, in order to increase employee productivity and development. For that, performance evaluation can run with periodic performance assessments that are oriented towards the past or the future. Employee performance assessment is intended to determine whether the form of employee performance has met the expected work standards. Employee performance at each agencies must be optimized in order to achieve the goals of the agency. Therefore, performance evaluation is very important and encourages employee performance to continue to be improved by looking at the results of the performance assessment given. By implementing performance evaluation on human resources in the company, it is an effort that can answer the success or failure of the company's goals that have been set. The employee work assessment/performance evaluation must be carried out in the form of periodic performance assessments.